2014
DOI: 10.1038/nphys3106
|View full text |Cite
|
Sign up to set email alerts
|

Perfect energy-feeding into strongly coupled systems and interferometric control of polariton absorption

Abstract: The ability to feed energy into a system, or -equivalently -to drive that system with an external input is a fundamental aspect of light-matter interaction. The key concept in many photonic applications is the "critical coupling" condition [1,2]: at criticality, all the energy fed to the system via an input channel is dissipated within the system itself. Although this idea was crucial to enhance the efficiency of many devices, it was never considered in the context of systems operating in a non-perturbative re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 31 publications
(22 reference statements)
2
71
0
Order By: Relevance
“…Interestingly, this general concept also holds for the regime of strong coupling, as developed in Ref. 28 . To this scope, it is necessary to add an additional oscillator to model the ISB plasmon, and introduce the light-matter coupling constant 29 .…”
mentioning
confidence: 78%
“…Interestingly, this general concept also holds for the regime of strong coupling, as developed in Ref. 28 . To this scope, it is necessary to add an additional oscillator to model the ISB plasmon, and introduce the light-matter coupling constant 29 .…”
mentioning
confidence: 78%
“…Recently it has been shown that the light fields coupled to an optical cavity with an intra-cavity absorber can be completely absorbed and no light can escape through the cavity [3][4][5][6][7][8]. Such a cavity-absorber system acts as a coherent perfect absorber and may be useful for a variety of fundamental studies and practical applications [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it requires that the imaginary (absorptive) part of the refractive index of the absorber is equal in absolute value to that of the gain medium at the lasing threshold and the incident light fields match the time-reversed lasing fields. Such perfect coherent absorber and the resulting interferometric control may have practical applications in optics communications and photonic devices such as transducers, modulators, and optical switches and transistors [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of perfect photon absorption are in the linear absorption regime, in which either a linear absorber is considered (such as in a solid-state Fabry-Perot etalon [6][7][8][9][10][11][12]) or in CQED, only the linear excitation of the first-order polariton states [19][20][21][22][23][24][25] are considered [19] and the multiphoton excitation of the higher-order polariton states in CQED are excluded [26][27]. Naturally this raises a question on whether coherent perfect photon absorption can occur in an optical system with a nonlinear absorber.…”
Section: Introductionmentioning
confidence: 99%